Associação do ácido úrico sérico com o consumo alimentar e metabólitos da cafeína na urina na população dos estados unidos. NHANES 2011-2012 - Limirio, Larissa Silva (2023)
Introduction: Hyperuricemia, is a condition characterized by elevated levels of uric acid (UA) in the body, has been extensively studied to understand its associations with dietary factors and caffeine metabolites. However, it is important to note that the results of these studies are controversial, making the understanding of the relationship between diet and UA a field still under development. In addition to evaluating dietary intake, it is essential to consider the association of UA with biochemical markers that more accurately predict consumption, such as caffeine metabolites present in the body. Objective: To evaluate the association of dietary intake and caffeine metabolites with serum UA levels. Methods: A cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2011-2012. The sample consisted of 3956 adults aged over 20 years and a subsample of 1252 individuals with information on caffeine and its metabolites in urine. Dietary intake was assessed through two 24-hour dietary recalls. The presence of caffeine and 15 of its metabolites in urine was evaluated by LC-tandem MS with electrospray ionization. Serum UA was measured by the colorimetric method. Linear and logistic regressions were performed for the associations. Results: In linear regression analyses, carbohydrate intake (β=-0.001; p=0.043), saturated fat intake (β=-0.020; p=0.015), fiber intake (β=-0.018; p=0.012), calcium intake (β=- 0.004; p=0.006), magnesium intake (β=-0.008; p=0.050), and cereal intake (β=-0.009; p=0.029) were inversely associated with serum UA levels, whereas alcohol intake (β=0.010; p<0.001) was positively associated with serum UA levels. In logistic regression analyses, alcohol intake (OR=1.02, 95% CI= 1.007 - 1.037) was associated with a higher chance of hyperuricemia, while vegetable intake (OR=0.99, 95% CI= 0.989 – 0.998) was associated with a lower chance of hyperuricemia. Dietary factors explained serum UA levels from 0.1% to 1.0%. Caffeine metabolites, including paraxanthine (β= -0.004, p= 0.006), theobromine (β= -0.004, p= <0.001), 7-methyluric acid (β= -0.003, p= 0.0033), 3,7-dimethyluric acid (β= -0.029, p= 0.024), 3- methylxanthine (β= -0.001, p= 0.038), and 7-methylxanthine (β= -0.001, p= 0.001), were inversely associated with serum UA levels, while 1,3-dimethyluric acid (β= 0.001, p= 0.012) was positively associated with serum UA levels. In logistic regression analyses, theobromine, 3-methyluric acid, 7-methyluric acid, and 3-methylxanthine were associated with a lower chance of hyperuricemia. Conclusion: This study highlights that carbohydrate intake, saturated fat intake, fiber intake, calcium intake, magnesium intake, and cereal intake are inversely associated with serum UA levels, while alcohol intake shows a positive association. Furthermore, theobromine and its metabolites, along with paraxanthine, exhibited an inverse association with serum UA levels, while 1,3-dimethyluric acid showed a positive association. These studies emphasize the importance of dietary factors and metabolites and their association with serum UA.